2004
DOI: 10.1007/s00134-003-2141-0
|View full text |Cite
|
Sign up to set email alerts
|

Albumin dialysis: a new therapeutic strategy for intoxication from protein-bound drugs

Abstract: The results of the study show that MARS can remove both albumin and other protein-bound drugs efficiently from the plasma, and it may have a place for the treatment of patients suffering from intoxication with this class of compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 13 publications
(9 reference statements)
3
40
0
3
Order By: Relevance
“…While midazolam was removed against a concentration gradient (dialysate concentration Ͼ plasma concentration), plasma fentanyl levels remained higher than those in the dialysate, suggesting that fentanyl it was removed along the concentration gradient. 3 As also suggested by Evenepoel et al, these data support the hypothesis that only the free drug is actually being removed by the MARS membrane, with constant re-equilibration of the free and bound components in the plasma and without any actual "stripping" of the drug from its binding protein by the membrane.…”
Section: Factors Determining Transfer Of Albumin-bound Toxinssupporting
confidence: 81%
See 1 more Smart Citation
“…While midazolam was removed against a concentration gradient (dialysate concentration Ͼ plasma concentration), plasma fentanyl levels remained higher than those in the dialysate, suggesting that fentanyl it was removed along the concentration gradient. 3 As also suggested by Evenepoel et al, these data support the hypothesis that only the free drug is actually being removed by the MARS membrane, with constant re-equilibration of the free and bound components in the plasma and without any actual "stripping" of the drug from its binding protein by the membrane.…”
Section: Factors Determining Transfer Of Albumin-bound Toxinssupporting
confidence: 81%
“…This gradient is much more pronounced than observed in the in vitro experiments by Steiner et al. 1,3 Despite the preservation of this important gradient for the length of the albumin dialysis session (Fig. 1), the clearance of tB declines over time and becomes negligible and even negative after 6 hours.…”
Section: To the Editorsmentioning
confidence: 65%
“…Several controlled clinical trials have shown that MARS therapy is an effective treatment for HE. [11][12][13][14][15][16] The mechanism by which MARS treatment results in improved HE is not clear, as results showing a reduction in blood ammonia with MARS have been inconsistent. In keeping with the results in humans, we recently showed attenuation in the rise in ICP (following a 4-hour MARS treatment) in a porcine model of ALF (induced by liver devascularization).…”
mentioning
confidence: 99%
“…In their recent experimental study, Sen et al (1) showed that Molecular Adsorbents Recirculating System (MARS ® ) could remove efficiently both albumin and protein-bound drugs from the plasma. The authors herein report the first case of successful blood detoxification using MARS ® therapy allowing full recovery in a patient presenting with a refractory shock secondary to acute diltiazem poisoning.…”
Section: To the Editormentioning
confidence: 99%